1986
DOI: 10.1177/001872678603900103
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Consequences of Exit, Voice, Loyalty, and Neglect: Responses to Dissatisfaction in Adult Romantic Involvements

Abstract: A survey of adult romantic involvements was conducted to test hypotheses regarding the determinants and consequences of four characteristic responses to dissatisfaction: exit, voice, loyalty, and neglect. In general, greater prior satisfaction with relationships and greater investment of resources in relationships were associated with stronger tendencies to react to problems constructively, with voice and loyalty, and lesser tendencies to react destructively, with exit and neglect. Higher quality alternatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 23 publications
8
86
1
3
Order By: Relevance
“…Moreover, accommodation has been tied to positive relational outcomes. Accommodation is positively associated with concurrent measures of relationship wellbeing and satisfaction (e.g., Rusbult et al, 1991;Rusbult, Johnson, & Morrow, 1986) and impressively predicts greater satisfaction and stability over time (Rusbult, Bissonnette, et al, 1998). In addition, research has begun to identify mechanisms through which relationships are enhanced by accommodative behavior.…”
Section: Neglectmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, accommodation has been tied to positive relational outcomes. Accommodation is positively associated with concurrent measures of relationship wellbeing and satisfaction (e.g., Rusbult et al, 1991;Rusbult, Johnson, & Morrow, 1986) and impressively predicts greater satisfaction and stability over time (Rusbult, Bissonnette, et al, 1998). In addition, research has begun to identify mechanisms through which relationships are enhanced by accommodative behavior.…”
Section: Neglectmentioning
confidence: 99%
“…For example, stronger use of constructive (prorelationship) responses and lower destructive (self-protective) responses are associated with retrospective self-reports of greater problem resolution (Rusbult et al, 1986). In addition, by aggregating ratings of dissatisfying incidents experienced over a two-week period, Drigotas, Whitney, and Rusbult (1995) found that pro-relationship reactions were perceived to have a more constructive impact on the problem and the relationship, whereas the opposite findings emerged for the self-protective responses of exit and neglect.…”
Section: Neglectmentioning
confidence: 99%
“…Research in social psychology has found that creating new interpersonal relationships becomes more difficult with age (Cumming and McCaffrey 1961;Davies and Griew 1963) and that older individuals are more willing to engage into the continuance of a relationship (even in problem situations) than younger people (e.g., Bloom et al 1977;Rusbult et al 1986). Furthermore, it can be the case that adjusting to a new product is more difficult for older customers so that they are more willing to return to a known provider.…”
Section: Framework Of the Studymentioning
confidence: 99%
“…the interaction of these two dimensions allows four types of behavior to be distinguished. the two constructive problem-solving strategies in the relationship are active dialogue and passive loyalty, and the two destructive strategies are active exit and passive neglect (Rusbult, zembrodt, & gunn, 1982;Rusbult, Johnson, & morrow, 1986).…”
Section: Conflict Resolution Strategiesmentioning
confidence: 99%
“…The Conflict Resolution Strategy questionnaire was constructed by Kriegelewicz (2003), based on the "Problem solving Patterns" questionnaire authored by Rusbult, Johnson and morrow (1986). the questionnaire comprises 32 items that make up four scales: dialogue, loyalty, exit and neglect.…”
Section: Research Toolsmentioning
confidence: 99%